Bringing Africa In: Promising Directions for Management Research - George, Gerard; Corbishley, Christopher; Khayesi, Jane N. O.; Haas, Martine R.; Tihanyi, Laszlo (Academy of Management Journal, 2016)
Africa is beginning to capture the imagination of entrepreneurs, corporate executives, and scholars as an emerging market of new growth opportunities. Over 15 years, the continent has experienced an average growth rate of 5% (World Economic Forum, 2015: v). Out of its 54 countries, 26 have achieved middleincome status, while the proportion of those living in extreme poverty has fallen from 51% in 2005 to 42% in 2014 (African Development Bank, 2014a: 49). Although there are regional differences, the primary drivers of growth have been rapidly emerging consumer markets, regional economic integration, investment in infrastructure, technological leap-frogging, and the opening up of new markets, especially in the service sector. African economies also face commensurate challenges. Across the continent, economies remain largely agrarian, underpinned by resource-driven growth and still dominated by the informal sector. But what is it about the context that makes Africa such fertile territory for management scholarship?